Management of Acute Myeloid Leukemia: Current Treatment Options and Future Perspectives - Maximilian Fleischmann (MDPI AG, 2021)
Treatment of acute myeloid leukemia (AML) has improved in recent years and several new therapeutic options have been approved. Most of them include mutation-specific approaches (e.g., gilteritinib for AML patients with activating FLT3 mutations), or are restricted to such defined AML subgroups, such as AML-MRC (AML with myeloid-related changes) or therapy-related AML (CPX-351). With this review, we aim to present a comprehensive overview of current AML therapy according to the evolved spectrum of recently approved treatment strategies. We address several aspects of combined epigenetic therapy with the BCL-2 inhibitor venetoclax and provide insight into mechanisms of resistance towards venetoclax-based regimens, and how primary or secondary resistance might be circumvented. Furthermore, a detailed overview on the current status of AML immunotherapy, describing promising concepts, is provided. This review focuses on clinically important aspects of current and future concepts of AML treatment, but will also present the molecular background of distinct targeted therapies, to understand the development and challenges of clinical trials ongoing in AML patients.